A foresight process as an institutional sensemaking tool. Issue 1 (9th February 2015) - Vuori, Johanna
Abstract : Purpose: – The purpose of this paper is to examine how a foresight project supports institutional positioning efforts through joint sensemaking. Design/methodology/approach: – This paper describes a case study that investigated the design, implementation, and outcomes of a foresight project at a Finnish higher education institution that selected sales and services as its institutional focus areas. According to the institutional strategy, all students should have acquired solid sales and service skills before the completion of their studies. The foresight methods used in this study were e-Delphi, futures workshops, and futures narratives. The data gathered in this iterative foresight process resulted in the delineation of eight future sales and service roles and their related competences, which were subsequently used for redesigning curricula, new programme development, and personnel training. Findings: – With the careful choice of foresight methods, the organisation was not only able to define future competence needs based on the collective wisdom of its stakeholders, but also fostered the organisation's strategic transformation process. Practical implications: – This paper gives insight into how to use a foresight process to foster institution-wide change. Originality/value: – This is one of only a few studies on how higher education institutions could implement their positioning strategies.